MAPPING MISCONCEPTIONS OF SENIOR HIGH SCHOOL STUDENTS IN PHYSICS: A QUALITATIVE PERSPECTIVE - Utama, Rodika; Moh. Toifur; Carissa Viola Putri Alfian; Nisrina Karimah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Misconceptions in physics represent a persistent barrier in students’ learning processes, influencing how they interpret and apply fundamental principles. These misconceptions are often robust, deeply rooted in everyday experiences, cultural beliefs, or misleading linguistic expressions, making them resistant to traditional forms of instruction. The present study aims to map senior high school students’ misconceptions across a wide range of core physics topics—including mechanics, energy, waves, and optics—through a qualitative lens. The research employed a four-tier diagnostic test and semi-structured interviews administered to 45 eleventh-grade students from a public high school in South Tangerang, Indonesia. The diagnostic test allowed for the identification of misconceptions by probing students’ answers, reasoning, confidence levels, and justifications, while follow-up interviews provided deeper insights into students’ thought processes. Data were analyzed thematically to classify the most dominant misconceptions and to uncover the underlying reasoning patterns that sustain them. Findings revealed that the most prevalent misconceptions were associated with Newton’s third law, where students believed that action and reaction forces cancel each other out; with energy conservation, where energy was perceived as a consumable entity that “runs out”; with sound propagation, where students assumed sound could travel in a vacuum; and with optics, particularly shadow formation, where students believed that light rays could stop or bend arbitrarily in space. These misconceptions were not isolated errors but rather formed coherent alternative frameworks that strongly influenced students’ conceptualizations. The implications of this study are twofold. First, mapping misconceptions across different physics domains provides a comprehensive overview of the conceptual challenges faced by students, which can inform teachers’ pedagogical strategies. Second, the results emphasize the need for instructional approaches that combine multiple representations—verbal, graphical, and experimental—along with inquiry-based activities that explicitly challenge students’ existing ideas. Such approaches are expected to foster conceptual change and support students in developing a more scientifically accurate understanding of physics.